Relationship Between Stunting and Cognitive Development of Tkit Ruhul Jihad Cilandak South Jakarta Students - Haris, Vera Suzana Dewi; Rahmadani, Siti; Syaripah, Rosita (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
According to the Ministry of Health (2018), the incidence of stunting in Indonesia has the highest prevalence compared to other nutritional problems such as undernutrition, thinness, and fatness. The prevalence of stunting has increased from 2016 (27.5%) to 29.6% in 2017. The purpose of this study was to determine the relationship between stunting and children's cognitive development. Research Methods: Observational quantitative research design is a cross-sectional method. The subject of this study was secondary data from TKIT Ruhul jihad Cilandak in the form of student development report documents consisting of age, height, and weight. The subjects in this study were student development report documents as many as 45 students with a simple randomization sampling method by the inclusion and exclusion criteria. A total of 22.2% of TKIT Ruhul Jihad students were stunted, and 88.9% of students had appropriate cognitive development, so from the results of the Fisher Exact test it was stated that there was no relationship between stunting and student cognitive development, based on Weight/Age it was known that three (6.7%) subjects had Weight/Age values less. Based on Height/Age, it is known that ten (22.2%) subjects have short Height/Age values. Based on Weight/Height, it is known that one (2.2%) subject has a Weight/Height value of less. This study concludes that there is no relationship between stunting and the cognitive development of TKIT Ruhul Jihad students in Cilandak, South Jakarta.